Aflatoxin B1-Associated DNA Adducts Stall S Phase and Stimulate Rad51 foci in Saccharomyces cerevisiae. (11th October 2010) - Fasullo, Michael; Chen, Yifan; Bortcosh, William; Sun, Minzeng; Egner, Patricia A.
Abstract : AFB1 is a potent recombinagen in budding yeast. AFB1 exposure induces RAD51 expression and triggers Rad53 activation in yeast cells that express human CYP1A2. It was unknown, however, when and if Rad51 foci appear. Herein, we show that Rad53 activation correlates with cell-cycle delay in yeast and the subsequent formation of Rad51 foci. In contrast to cells exposed to X-rays, in which Rad51 foci appear exclusively in G2 cells, Rad51 foci in AFB1 -exposed cells can appear as soon as cells enter S phase. Although rad51 and rad4 mutants are mildly sensitive to AFB1, chronic exposure of the NER deficient rad4 cells to AFB1 leads to increased lag times, while rad4 rad51 double mutants exhibit synergistic sensitivity and do not grow when exposed to 50 μ M AFB1 . We suggest RAD51 functions to facilitate DNA replication after replication fork stalling or collapse in AFB1 -exposed cells.